2020
DOI: 10.1186/s12889-020-09617-1
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of routine vitamin A supplementation for children in Humbo district, southern Ethiopia: community-based cross-sectional study

Abstract: Background In low- and middle-income countries routine vitamin A supplementation (VAS) is a key strategy for reducing vitamin A deficiency and mortality and morbidity of preschool children. However, in Ethiopia, there is paucity of evidence regarding the level and determinants of the uptake of the supplement. This study was designed to assess the coverage and predictors of VAS among preschool children in Humbo district, Southern Ethiopia. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 18 publications
3
50
2
4
Order By: Relevance
“…20 The employment rate might depend on education 23 and exposure to the importance of supplements. 24 In addition, this study also revealed that paternal education is found to be negatively associated with childhood deworming, unlike other studies in which paternal education status is supportive for child healthcare practices. 25 Children whose fathers attend secondary and above, and primary level of education were 50% and 29% less likely to get deworming supplementation than children whose fathers didn't attend formal education, respectively.…”
Section: Discussioncontrasting
confidence: 56%
“…20 The employment rate might depend on education 23 and exposure to the importance of supplements. 24 In addition, this study also revealed that paternal education is found to be negatively associated with childhood deworming, unlike other studies in which paternal education status is supportive for child healthcare practices. 25 Children whose fathers attend secondary and above, and primary level of education were 50% and 29% less likely to get deworming supplementation than children whose fathers didn't attend formal education, respectively.…”
Section: Discussioncontrasting
confidence: 56%
“…To the best of the authors' knowledge, only one recent study was carried out in the other corner of southern Ethiopia. The study revealed that two-thirds of children between 6 and 59 months of age have received VAS [ 15 ]. Therefore, this study aimed to assess the current VAS coverage and ocular signs among children aged 6–59 months in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, eighteen studies that met the selection criteria were included in the systematic review ( Fig. 1 ) ( 14 – 31 ) .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies were conducted in the WHO Africa Region ( 14 – 17 , 19 25 , 27 31 ) and three in the WHO South-East Asia Region ( 15 , 18 , 26 ) during the period 2001–2020. When appraised for quality, only five studies were categorised as high quality ( 19 , 21 , 25 , 29 , 30 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation